Salutary Neglect : Colonial Administration Under the Duke of Newcastle - Henretta, James A. (Book collections on Project MUSE., 1972)
During the remarkably long period (1724-1754) that Thomas Pelham-Holles, Duke of Newcastle, served as England's secretary of state, private interests and the exigencies of domestic politics rather than a rational assessment of England's stake in America determined colonial policy. As no purposeful effort was made to administer the colonies" political life, they enjoyed in effect relatively little interference in their internal affairs. The reasons for this "salutary neglect" and the lack of a vigorous colonial program arc analyzed now by James Henretta. His study, though focusing on the politics and patronage of the Duke, brings into view the entire range of men and agencies that had a hand in making colonial policy and dispensing patronage. It thus illuminates the political and administrative system that developed in England during the first half of the century and continued in effect at the time of the American Revolution.Originally published in 1972.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.